1985
DOI: 10.1136/jcp.38.11.1247
|View full text |Cite
|
Sign up to set email alerts
|

Fertility in young men and women after treatment for lymphoma: a study of a population.

Abstract: SUMMARY All young patients in the Grampian area attending the lymphoma review clinic who had received first line treatment for Hodgkin's disease and had attained complete remission without subsequent relapse were studied between 1980 and 1983. Chemotherapy with MVPP (mustine, vinblastine, procarbazine, and prednisolone) had more severe effects on the fertility of men than that of women; younger women and those taking oral contraceptives were more likely to retain fertility than those over 30 or not taking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…10 The information on the effects of chemotherapy on early menopause, however, is still limited. Studies suffer from several shortcomings, including small sample size [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and lack of detailed information on treatment exposures. 29,30 Although in most cases only acute gonadotoxic effects and chemotherapy-related amenorrhea have been studied rather than long-term effects on premature menopause, it can be concluded that alkylating agents are the most hazardous chemotherapeutic agents, and that gonadotoxicity is dose dependent.…”
Section: Introductionmentioning
confidence: 99%
“…10 The information on the effects of chemotherapy on early menopause, however, is still limited. Studies suffer from several shortcomings, including small sample size [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and lack of detailed information on treatment exposures. 29,30 Although in most cases only acute gonadotoxic effects and chemotherapy-related amenorrhea have been studied rather than long-term effects on premature menopause, it can be concluded that alkylating agents are the most hazardous chemotherapeutic agents, and that gonadotoxicity is dose dependent.…”
Section: Introductionmentioning
confidence: 99%
“…24 It has been proposed that ovarian suppression with oral contraceptives (OCs) or gonadotropin releasing hormone agonists (GnRH-agonist) may reduce the gonadotoxic effects of cancer therapy. [25][26][27][28] Oral contraceptives and GnRH-agonists produce reversible suppression of gonadotropin secretion causing secondary inhibition of follicle growth beyond the multilayered granulosa cell stage. The hypothesis, from observational studies of prepubescent gonadal resistance to gonadotoxic therapy, supposes that a quiescent ovary, with a reduced number of active follicles and more resting follicles, will reduce the damage caused by gonadotoxic therapies.…”
Section: Ovarian Protectionmentioning
confidence: 99%
“…28 The same has been proposed of OCs and GnRH-agonist in small, retrospective, poorly designed, human studies. [25][26][27] In addition, there are biologically implausible aspects surrounding ovarian protection through gonadotropin suppression. For example, the recruitment of resting follicles is gonadotropin independent and not until the final stages of growth does the follicle need gonadotropin support.…”
Section: Ovarian Protectionmentioning
confidence: 99%
“…Ovarian function was evaluated in women following treatment with combination chemotherapy (Table 2) [18][19][20][21]. These studies, performed following treatment with the combination of nitrogen mustard, vincristine, procarbazine and prednisone (MOPP); the combination of nitrogen mustard, vinblastine, procarbazine, and prednisone (MVPP); or the combination of chlorambucil, vinblastine, procarbazine and prednisone (ChlVPP) demonstrated the sensitivity of the older patient to the gonadal toxicity of such therapy (Table 3) [22][23][24][25], whether three or six cycles were administered (Table 4) [26].…”
Section: Ovarymentioning
confidence: 99%
“…Combination chemotherapy which includes an alkylating agent and procarbazine causes severe damage to the testicular germinal epithelium (Table 5) [19][20][21][51][52][53][54][55][56][57][58][59][60]. Azoospermia was present in all men by the start of the third cycle of MVPP chemotherapy [56], and less than 20% of men had recovery of spermatogenesis when evaluated 37-48 months after treatment, suggesting that recovery of spermatogenesis in this population of patients was infrequent [55].…”
Section: Testismentioning
confidence: 99%